Spatial Differentiation of Labor Markets from the Labor Demand Perspective - Małgorzata Gawrycka; Anna Szymczak (Contemporary Economics, 2010)
The labor market is not a homogenous category. Its diversity is a consequence of the specificity of the region, its structure and level of development. In order to examine the competitive advantages of local labor markets, in terms of conditions associated with the operation of businesses, one shall specify characteristics determining features the potential of the region. The multitude of these features makes it difficult to choose measures that could enrich picture of diversity of labor markets. This aim of a paper is to assess the spatial differentiation of labor markets from the labor demand perspective. In the paper the taxonomic methodology was applied.